IMPACT OF SIMULTANEOUS VS. DELAYED VENTRICULOPERITONEAL SHUNTING ON WOUND HEALING IN HYDROCEPHALUS PATIENTS UNDERGOING MENINGOMYELOCELE REPAIR - Dr Muhammad Jahangir Khan; Dr Junaid Mubashir Cheema; Dr Gulzar Aslam; Dr Amna Ehsan; Dr Ather Adnan; Muhammad Faheem Anwer (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Introduction: Neural tube defects (NTD) are one of the most common congenital defects causing disability in children worldwide. They also represent one of the most intricate lesions which yet can be addressed surgically and do not preclude long term survival.Objective: The main objective of the study is to compare the outcome of simultaneous ventriculoperitoneal shunting as compared to delayed VP shunting in terms of wound healing according to Southampton wound grading system.Methodology of the study: This Randomized Control Trial was conducted in the Neurosurgery Department Gujranwala Medical College Teaching Hospital during April 2023 till March 2024. Data were collected through non-probability consecutive sampling. The sample size turned out to be 110 in each group were included in this study.All children (male and female) with congenital myelomeningocele along with hydrocephalus diagnosed on Magnetic Resonance Imaging (MRI) Spine and CT Scan Brain respectively were included in the study.Results: The study included 220 patients, with 110 in the simultaneous group and 110 in the delayed group. The demographic characteristics of the two groups were comparable, with no significant differences in age, gender, or baseline clinical parameters. The average length of hospital stay was significantly shorter in the simultaneous group (15.2 ± 3.1 days) compared to the delayed group (18.6 ± 3.5 days, p